Urokinase type plasminogen activator receptor expression in colorectal neoplasms. Issue 6 (1st December 1998) - Suzuki, S; Hayashi, Y; Wang, Y; Nakamura, T; Morita, Y; Kawasaki, K; Ohta, K; Aoyama, N; Kim, S R; Itoh, H; Kuroda, Y; Doe, W F
Abstract : Background —The urokinase type plasminogen activator receptor (uPAR) may play a critical role in cancer invasion and metastasis. Aims —To study the involvement of uPAR in colorectal carcinogenesis. Methods —The cellular expression and localisation of uPAR were investigated in colorectal adenomas and invasive carcinomas by in situ hybridisation, immunohistochemistry, and northern and western blot analyses. Results —uPAR mRNA expression was found mainly in the cytoplasm of dysplastic epithelial cells of 30% of adenomas with mild (19%), moderate (21%), and severe (47%) dysplasia, and in that of carcinomatous cells of 85% of invasive carcinomas: Dukes' stages A (72%), B (93%), and C (91%). Some stromal cells in the adjacent neoplastic epithelium were faintly positive. Immunoreactivity for uPAR was detected in dysplastic epithelial cells of 14% of adenomas and in carcinomatous cells of 49% of invasive carcinomas. uPAR mRNA and protein concentrations were significantly higher in severe than in mild or moderate dysplasia (p<0.05); they were notably higher in Dukes' stage A than in severe dysplasia (p<0.05), and significantly higher in Dukes' stage B than in stage A (p<0.05), but those in stage B were not different from those in stage C or in metastatic colorectal carcinomas of the liver. Conclusions —Colorectal adenoma uPAR, expressed essentially in dysplastic epithelial cells, was upregulated with increasing severity of atypia, and increased notably during the critical transition from severe dysplasic adenoma to invasive carcinoma. These findings implicate uPAR expression in the invasive and metastatic processes of colorectal cancer.